Cu(i)-catalyzed microwave-assisted synthesis of 1, 2, 3-triazole linked with 4-thiazolidinones: a one-pot sequential approach. Issue 2 (4th December 2014) - Kumar, Yogesh; Matta, Akanksha; Kumar, Prashant; Parmar, Virinder S.; Van der Eycken, Erik V.; Singh, Brajendra K.
Abstract : A novel copper(i ) catalyzed, microwave-assisted, one-pot, four-component, sequential reaction has been developed for the synthesis of 3-phenyl-2-[4-{(1-phenyl-1 H -1, 2, 3-triazol-4-yl)methoxy}phenyl]thiazolidin-4-ones. Abstract : A novel copper(i ) catalyzed, microwave-assisted one-pot, four-component sequential reaction between a propargyloxybenzaldehyde, a substituted phenyl azide, a substituted aniline and thioglycolic acid has been developed for the synthesis of 3-phenyl-2-[4-{(1-phenyl-1 H -1, 2, 3-triazol-4-yl)methoxy}phenyl]thiazolidin-4-ones.